Calibration of DEM parameters for coated sunflower seeds based on dynamic stacking angle - Liu, Changji; Zhao, Wuyun; Feng, Bin; Shi, Linrong; Sun, Bugong; Dai, Fei; Li, Hui (International Journal of Agricultural and Biological Engineering, 2026)
To address the errors associated with the application of existing Discrete Element Method simulation parameters in roller-type precision seeders, this study focused on calibrating the key contact parameters of the ‘Xinhe No. 1’ coated confectionary sunflower seeds, so as to provide a reliable simulation foundation for the optimization of the seeders. Through dynamic stacking angle experiments and comparative trials involving confectionary sunflowers (including Xinhe No. 1) and oil sunflowers with significantly different physical properties, the optimal working conditions for the rotating drum were determined as a rotation speed of 10 r/min, 304 Stainless Steel as the inner wall material, and a filling ratio of 30%. The study also clarified the variation patterns of the dynamic stacking angle. Physical experiments were conducted to measure the static friction coefficients, restitution coefficients, and inter-seed restitution coefficients between Xinhe No. 1 seeds and three materials: 304 Stainless Steel, Q235 Steel, and ABS Plastic. The physical dynamic stacking angle was obtained via a rotating drum experiment. A single-factor experiment was used to determine the range of simulation parameters, and a second-order orthogonal experiment was conducted using Design-Expert software to optimize contact parameters with the physical dynamic stacking angle as the target. The parameters were subsequently validated using the Discrete Element Method (DEM) simulation software EDEM 2022.3, hereinafter abbreviated as EDEM simulations. Finally, rolling friction coefficients between seeds and Q235 Steel and ABS Plastic were obtained through both simulation and physical experiments using alternative contact materials. The results showed that the static friction coefficients between Xinhe No. 1 and 304 Stainless Steel, Q235 Steel, and ABS Plastic were 0.32, 0.36, and 0.25, respectively; the restitution coefficients were 0.42, 0.39, and 0.32; and the rolling friction coefficients were 0.012, 0.011, and 0.010. The measured values of the inter-seed static friction coefficient, restitution coefficient, and rolling friction coefficient were 0.31, 0.43, and 0.010, respectively. The relative error between simulated and physical stacking angles was <1.5%. Calibrated DEM parameters for Xinhe No. 1 coated sunflower seeds provide a theoretical basis for optimizing the design of sunflower precision seeders. Keywords: sunflower seed, DEM, parameter calibration, dynamic stacking angle, hill-drop planter DOI: 10.25165/j.ijabe.20261901.10103 Citation: Liu C J, Zhao W Y, Feng B, Shi L R, Sun B G, Dai F, et al. Calibration of DEM parameters for coated sunflower seeds based on dynamic stacking angle. Int J Agric & Biol Eng, 2026; 19(1): 283–294.